Le bout du monde est une fenêtre roman - Prophète, Emmelie 1971- (Mémoire d'encrier, 2015)
Emmelie Prophète (1971) is a Haitian journalist and writer. She has collaborated with several literary journals such Chemins Critiques, Boutures, Casa de las Americas, Cultura, La Nouvelle Revue Française. From 2006 to 2011 she was head of the Direction Nationale du Livre, Ministère de la culture en Haïti and is currently responsible for the cultural supplement of the Haitian daily, Le Nouvelliste as well as Director of the Haitian Bureau of Copyright and Director of the Bibliothèque Nationale d'Haïti. She has also published Des marges à remplir (2000, poems) et Sur parure d'ombre (2004, poems), Le Testament des solitudes (2007, stories) and Le désir est un visiteur silencieux (2014, short story)